Duodenal gossypiboma: a case report and literature review. - Velasco, Stephany; Díaz, Marialy; Cova, Tamarys; Hopp, Evelyn; Rodriguez, Roselin; Chirinos, Yeirama; Carreiro, Manuel (Investigación Clínica, 2015)
Gossypiboma is a retained surgical cotton matrix material in the body after a surgical procedure. Cases are rarely reported due to medico-legal concerns. Although infrequent, it causes serious morbidity and even mortality if left undiagnosed. We present the case of a trans-mural migration of gossypiboma and a review of the literature. Gossypiboma”™s trans-duodenal migration is a rare complication of retained gauzes. Cases reported in the literature were easy to diagnose based on clinical grounds and endoscopic studies.Â Â